Impacts of estrus expression and intensity during a timed-AI protocol on variables associated with fertility and pregnancy success in Bos indicus-influenced beef cows. (2nd February 2018) - Rodrigues, A D; Cooke, R F; Cipriano, R S; Silva, L G T; Cerri, R L A; Cruppe, L H; Meneghetti, M; Pohler, K G; Vasconcelos, J L M
Abstract: This experiment evaluated the impacts of estrus expression and intensity, estimated by physical activity during a timed-AI protocol, on reproductive performance of Bos indicus -influenced beef cows. A total of 290 lactating, primiparous, and multiparous nonpregnant Nelore × Angus cows received a 2 mg injection of estradiol benzoate and an intravaginal progesterone (P4 ) releasing device (CIDR ) on d −11, a 12.5 mg injection of PGF2α on d −4, CIDR removal in addition to 0.6 mg injection of estradiol cypionate and 300 IU injection of eCG on d −2, and timed-AI on d 0. Cows were fitted with a pedometer behind their left shoulder on d −4. An estrus detection patch was attached to the tail-head of each cow on d −2. Pedometer results were recorded on d −2 and 0. Estrus expression was defined as removal of >50% of the rub-off coating from the patch on d 0. Net physical activity during estrus was calculated by subtracting total steps from d −4 to −2 (nonestrus basal activity) from total steps from d −2 to 0 (proestrus + estrus period) of each cow. Cows that did not express estrus were classified as NOESTR . Cows that expressed estrus were ranked by net physical activity; those above the median were classified as HIESTR and the remaining cows as LWESTR . Ovarian ultrasonography was performed on d 0 and 7. Blood was collected on d 0, 7, 20, and 30. Pregnancy status was verified by ultrasonography on d 30. Only data from cows responsive to the estrus synchronization protocol were utilized (NOESTR, n = 59; LWESTR, n = 100; HIESTR, n = 98). Diameter of dominant follicle on d 0, corpus luteum volume on d 7, and plasma P4 concentrations on d 7 were greater ( P ≤ 0.05) in HIESTR vs. LWESTR and NOESTR and also greater ( P ≤ 0.05) for LWESTR vs. NOESTR. Plasma P4 concentrations on d 0 were greater ( P < 0.01) in NOESTR vs. HIESTR and LWESTR and similar ( P = 0.93) between HIESTR and LWESTR. Whole blood mRNA expression of myxovirus resistance 2 on d 20 was greater ( P ≤ 0.05) in HIESTR vs. LWESTR and NOESTR, and similar ( P = 0.72) between LWESTR and NOESTR. Pregnancy rates were less ( P ≤ 0.04) in NOESTR vs. HIESTR and LWESTR (52.4%, 68.9%, and 73.5%, SEM = 7.2), and similar ( P = 0.57) between HIESTR and LWESTR. Hence, expression of estrus during a timed-AI protocol improved ovarian dynamics and pregnancy success, whereas estrus intensity modulated key biological markers associated with fertility but not pregnancy rates in B. indicus -influenced cows beef cows.